2014
DOI: 10.1124/mol.113.091165
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-Derived Tryptophan Metabolites and Their Aryl Hydrocarbon Receptor-Dependent Agonist and Antagonist Activities

Abstract: The tryptophan metabolites indole, indole-3-acetate, and tryptamine were identified in mouse cecal extracts and fecal pellets by mass spectrometry. The aryl hydrocarbon receptor (AHR) agonist and antagonist activities of these microbiotaderived compounds were investigated in CaCo-2 intestinal cells as a model for understanding their interactions with colonic tissue, which is highly aryl hydrocarbon (Ah)-responsive. Activation of Ah-responsive genes demonstrated that tryptamine and indole 3-acetate were AHR ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
218
4
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 262 publications
(252 citation statements)
references
References 42 publications
(90 reference statements)
13
218
4
4
Order By: Relevance
“…The assay for metabolic activity of the tryptophan metabolites was determined using the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay essentially as described by Jin et al (2014) (Supplemental Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay for metabolic activity of the tryptophan metabolites was determined using the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay essentially as described by Jin et al (2014) (Supplemental Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that the gut microbiota produces metabolites that include AhR-active compounds that could potentially modulate AhR-mediated intestinal resiliency and responses to inflammatory stimuli (Li et al, 2009;Bansal et al, 2010;Zelante et al, 2013;Fukumoto et al, 2014;Venkatesh et al, 2014). Research in our laboratories has previously investigated the AhR activities of the tryptophan metabolites indole, indole-3-acetate, tryptamine, and 3-indoxyl sulfate using CYP1A1 induction as a prototypical AhR-dependent response in human CaCo2 colon cancer cells (Jin et al, 2014). In this report, we determined the AhR activity of tryptophan metabolites in a nontransformed young adult mouse coloncyte (YAMC) cell line (D'Abaco et al, 1996), and there were significant differences between YAMC versus CaCo2 cells with respect to the gene-specific AhR agonist and antagonist activities of tryptophan metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Le métabolisme du tryptophane est altéré chez les souris M Card9-/-➔ Ax Des études suggèrent que les catabolites du tryptophane générés par le microbiote intestinal ont un rôle dans la réponse immune mucosale via le récep-teur aryl-hydrocarbone (AhR) en modulant la production d'IL-22 [17,18]. AhR est un récepteur intracellulaire qui, par sa fonction de régulateur transcriptionnel, agit sur de nombreux gènes impliqués dans la détoxification, le déve-loppement ou la modulation du système immunitaire [17].…”
Section: Les Maladies Inflammatoires Chroniques De L'intestin (Mici)unclassified
“…AhR est un récepteur intracellulaire qui, par sa fonction de régulateur transcriptionnel, agit sur de nombreux gènes impliqués dans la détoxification, le déve-loppement ou la modulation du système immunitaire [17]. Le tryptophane peut être métabolisé soit par les bactéries intestinales en dérivés indoles, comme l'indole-3-acétique acide (IAA), soit par les cellules hôtes en kynurénine 3 [15,18]. Les dérivés indoles sont des ligands d'AhR connus pour induire une production locale d'IL-22 par les cellules immunitaires [18].…”
Section: Les Maladies Inflammatoires Chroniques De L'intestin (Mici)unclassified
See 1 more Smart Citation